Melestarikan Pengurusan dan Institusi Pemuziuman Borneo: Pengalaman Sarawak - Nur Auni Ugong; Bilcher Bala; Baszley Bee B. Basrah Bee (2018)
Cultural heritage management play an important role in preservation, protection, and conservation of the cultural heritage. The management of Sarawak's cultural heritage has been well organized since 1947, particularly on cultural heritage sites damaged during the Second World War. The existence of ministries and museum department brought a positive impact in preserving every planned and practiced management practice. Museum department plays a role in research, education, documentation, and collection. Hence, then just a museum created in 1891, Sarawak now has about 10 museums. This paper attempts to share the experience of success achieved by the Sarawak Museum Department as one of the oldest museums in Malaysia and Borneo.